Tackling ionospheric scintillation threat to GNSS in Latin America - Sreeja, Vadakke Veettil; Aquino, Marcio; Forte, Biagio; Elmas, Zeynep; Hancock, Craig; De Franceschi, Giorgiana; Alfonsi, Lucilla; Spogli, Luca; Romano, Vincenzo; Bougard, Bruno; Galera Monico, Joao Francisco [UNESP]; Wernik, Andrzej W.; et al. (Edp Sciences S A, 2011)
Scintillations are rapid fluctuations in the phase and amplitude of transionospheric radio signals which are caused by small-scale plasma density irregularities in the ionosphere. In the case of the Global Navigation Satellite System (GNSS) receivers, scintillation can cause cycle slips, degrade the positioning accuracy and, when severe enough, can even lead to a complete loss of signal lock. Thus, the required levels of availability, accuracy, integrity and reliability for the GNSS applications may not be met during scintillation occurrence; this poses a major threat to a large number of modern-day GNSS-based applications. The whole of Latin America, Brazil in particular, is located in one of the regions most affected by scintillations. These effects will be exacerbated during solar maxima, the next predicted for 2013. This paper presents initial results from a research work aimed to tackle ionospheric scintillation effects for GNSS users in Latin America. This research is a part of the CIGALA (Concept for Ionospheric Scintillation Mitigation for Professional GNSS in Latin America) project, co-funded by the EC Seventh Framework Program and supervised by the GNSS Supervisory Authority (GSA), which aims to develop and test ionospheric scintillation countermeasures to be implemented in multi-frequency, multi-constellation GNSS receivers.
Keywords: 2447: modelling and forecasting; 2400: ionosphere; 2415: equatorial ionosphere; 2439: ionospheric irregularities